Representation of a three-dimensional integrated survey of the Casa De Vidro by Lina Bo Bardi in São Paulo, Brazil: Methods and Techniques for Representing a Three-Dimensional Integrated Survey of Casa De Vidro in São Paulo (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This paper describes the method and the process used for the representation of the integrateddigital survey of the Casa De Vidro by Lina Bo Bardi in São Paulo (Brazil), carried out in 2017 by theDIAPReM (Development of Integrated Automatic Procedures for Restoration of Monuments) DepartmentCenter of the University of Ferrara. It is part of a Master‟s degree thesis which had as its objective thevalorization of the site as a museum. After a brief description of the house and an introduction to thethesis work, the text describes the characteristics of the laser scanner survey and the method ofextracting raster images as a support for architectural drawings. Subsequently, the strategy ofrepresenting the complex topography of the site is explored, aiming at the production of the situation plan.Given the importance of the tropical garden that surrounds the house, a further study concerns therepresentation of the vegetation on the vertical plane. The process that leads to the vectorization of theprofiles of the landscape starting from the extractions from the point cloud is described in detail. Then itis exposed the treatment of the raster image with the visualization in false colors of the reflectance datathrough filters to bring the colors to shades of green. By assembling the trees together, it is possible toget drawings that best represent the vegetation and the insertion of the architecture in the tropicalgarden. It is noted that, due to the high density of trees, it would not be possible to create arepresentation corresponding to each one of them. These circumstances forced to choose specificspecimens and to repeat them in the overall elaborates.